Assessment Of Speaking Skills (Maharah Al- Kalam) Of Students At Madrasah Aliyah Negeri (MAN) In Jambi City - Budi Sanjaya; Irfan Irfan (AIUA Journal of Islamic Education, 2019)
This study aims to evaluate the Arabic speaking skills of students at Madrasah Aliyah Negeri (MAN) in Jambi City. This research was carried out by using the evaluation method on the skills of MAN students by using two types of tests, answer questions and storytelling tests to assess seven elements in speaking aspects fluency, intonation, grammar, vocabulary mastery and understanding. Population in this study there were 240 students and the sample was 150 students. Data were analyzed by using SPSS (statistical Package for Science Social) to identify the frequency, percentage data, mean and standard deviation. Overall, the results of the study show that the Arabic speaking skills of the students MAN Jambi City students are still at a simple stage (mean = 3.09, SD = 0.64) for each element assessed.